2012
DOI: 10.1590/s1519-69842012000100025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the leaf anatomy in two Parodiolyra species (Poaceae: Olyreae) occurring on forests in Eastern Brazil

Abstract: Parodiolyra is a member of Olyreae, a tribe of herbaceous bamboo species within the Poaceae. The genus has five species, four of which were previously regarded as belonging to Olyra L. Parodiolyra has a Neotropical distribution and only two species occur on forests in Eastern Brazil: P. micrantha (Kunth) Zuloaga & Davidse and P. ramosissima (Trin.) Soderstr. & Zuloaga, the first widely distributed in the Neotropics while the second is endemic to the state of Bahia. Leaf anatomy of the two species was analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Long cells, short intercostal cells, and silicified cells were observed for the genre ( Figure 3A, 3B, 3C, 3D), as described by Ellis (1979) and registered to other species of Poaceae by Jesus Junior et al (2012).…”
Section: Resultssupporting
confidence: 62%
“…Long cells, short intercostal cells, and silicified cells were observed for the genre ( Figure 3A, 3B, 3C, 3D), as described by Ellis (1979) and registered to other species of Poaceae by Jesus Junior et al (2012).…”
Section: Resultssupporting
confidence: 62%
“…The studies made over the last decade have shown that the anatomy of the root, stalk and specially leaves, are consistent for the infra-generic or genus separation (Jesus Junior et al, 2012;Gomes et al, 2009;Lusa and Bona, 2009), especially for Papilionoideae (Teixeira and Gabrielli, 2006;Sartori and Tozzi, 2002;Crow et al, 1997). The anatomy is also applied in the interpretation of the phenotype plasticity in amphibious species located in lagoons and wetlands of Pantanal (Scremin-Dias, 1999;Scremin-Dias et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The strongly similar morphological features of Luziola species in the vegetative stage raised the need for systematic and phylogenetic studies to the genus (Martinez-y-Perez et al 2006a, b, 2008. Although surveys of anatomy of the leaf blade have revealed the utility of features in the delimitation of Poaceae (e.g., Metcalfe 1960;Tateoka 1963;Vieira et al 2002;Guglieri et al 2008;Pelegrin et al 2009;Jesus-Junior et al 2012), there is a dearth of information particularly among morphologically similar grasses in the vegetative stage.…”
Section: Introductionmentioning
confidence: 99%